Greenland - Waugh, Ric Roman, 1968-; Butler, Gerard, 1969-; Baccarin, Morena; Floyd, Roger Dale (Universal Pictures Home Entertainment, 2021)
As cities around the world are being destroyed by a comet, a family races against time to reach a possible safe haven.
Originally released as a motion picture in 2020.
Dolby digital 5.1, wide screen 2.39:1.
Gerard Butler, Morena Baccarin, Roger Dale Floyd, Scott Glenn, Randal Gonzalez.
MPAA rating: PG-13.
Closed-captioned.
Keywords: Comets -- Collisions with Earth -- Drama; Families -- Drama; Survival -- Drama; Disaster films; Survival films; Action and adventure films; Feature films; Fiction films; Video recordings for the hearing impaired